IT modernization using Catalogic ECX copy data management and IBM Spectrum Storage - Burns, Christine (IBM redbooks., 2016)
Data is the currency of the new economy, and organizations are increasingly tasked with finding better ways to protect, recover, access, share, and use data. Traditional storage technologies are being stretched to the breaking point. This challenge is not because of storage hardware performance, but because management tools and techniques have not kept pace with new requirements. Primary data growth rates of 35% to 50% annually only amplify the problem. Organizations of all sizes find themselves needing to modernize their IT processes to enable critical new use cases such as storage self-service, Development and Operations (DevOps), and integration of data centers with the Cloud. They are equally challenged with improving management efficiencies for long established IT processes such as data protection, disaster recovery, reporting, and business analytics. Access to copies of data is the one common feature of all these use cases. However, the slow, manual processes common to IT organizations, including a heavy reliance on labor-intensive scripting and disparate tool sets, are no longer able to deliver the speed and agility required in today's fast-paced world. Copy Data Management (CDM) is an IT modernization technology that focuses on using existing data in a manner that is efficient, automated, scalable, and easy to use, delivering the data access that is urgently needed to meet the new use cases. Catalogic ECX, with IBM® storage, provides in-place copy data management that modernizes IT processes, enables key use cases, and does it all within existing infrastructure. This IBM Redbooks® publication shows how Catalogic Software and IBM have partnered together to create an integrated solution that addresses today's IT environment.